2021
DOI: 10.1186/s12920-021-01012-y
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate transcriptome analysis identifies networks and key drivers of chronic lymphocytic leukemia relapse risk and patient survival

Abstract: Background Chronic lymphocytic leukemia (CLL) is an indolent heme malignancy characterized by the accumulation of CD5+ CD19+ B cells and episodes of relapse. The biological signaling that influence episodes of relapse in CLL are not fully described. Here, we identify gene networks associated with CLL relapse and survival risk. Methods Networks were investigated by using a novel weighted gene network co-expression analysis method and examining overr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Wound images were observed at the specified time points (0 h and 24 h). The scratch width (W) was determined, and the cell migration rate was calculated as (W0 h-W24 h)/W0 h × 100% [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wound images were observed at the specified time points (0 h and 24 h). The scratch width (W) was determined, and the cell migration rate was calculated as (W0 h-W24 h)/W0 h × 100% [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 D) and ZAP70 + increased as human U-CLL than M-CLL. Fzd2 is β-catenin dependent, and human CLL and ZAP70 + U-CLL showed expression of Wnt10a and Wnt6, which generated Fzd2 [ 78 ]. Ki67 (NKI67) is a proliferation-related antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Other extensive transcriptome analyses have also been carried out. Griffen et al [ 82 ] conducted a multivariate transcriptome analysis on 203 CLL patients, focusing on relapses. Between Binet stage A patients with and without relapse, 1703 genes were downregulated and 1250 were upregulated.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Certain hub genes within these modules have consequently been proposed as potential novel therapeutic targets or clinical markers. These include: ARHGAP27P2, C1S, CASC2, CLEC3B, CRY1, CXCR5, FUT5, MID1IP1 , and URAHP [ 82 ]. Sbarrato et al [ 83 ] showed that CLL B cells hold a ribosome-related signature with reduced expression of factors that modify ribosomal rRNA, including DKC1 .…”
Section: Transcriptomicsmentioning
confidence: 99%